2005
DOI: 10.1136/jnnp.2004.057992
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal stimulation in dystonia: effects on cognition, mood, and quality of life

Abstract: Bilateral deep brain stimulation (DBS) of the globus pallidus internus (GPi) alleviates symptoms in patients with dystonia but its effects on cognition, neuropsychiatric status, and quality of life have not been examined. This is a case series report of 15 consecutive patients with different forms of dystonia who underwent bilateral implantation of DBS electrodes in the GPi. The patients were evaluated preoperatively and after 3-12 months of DBS with tests of cognition (Mattis Dementia Rating Scale, Stroop Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 18 publications
5
105
2
4
Order By: Relevance
“…Another reason is that patients with major and active psychiatric issues have frequently been excluded from studies examining long-term postoperative outcomes with reported results being mostly limited to patients without major psychiatric difficulties before surgery. [13][14][15][16][17][18][19] However, 3 suicides have been reported so far within 14 months after bilateral GPi DBS. 20,21 Moreover, studies reporting neuropsychiatric outcomes in various types of dystonia (primary generalized, cervical, and secondary dystonia) and in the long-term follow-up are lacking.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…Another reason is that patients with major and active psychiatric issues have frequently been excluded from studies examining long-term postoperative outcomes with reported results being mostly limited to patients without major psychiatric difficulties before surgery. [13][14][15][16][17][18][19] However, 3 suicides have been reported so far within 14 months after bilateral GPi DBS. 20,21 Moreover, studies reporting neuropsychiatric outcomes in various types of dystonia (primary generalized, cervical, and secondary dystonia) and in the long-term follow-up are lacking.…”
Section: Classification Of Evidencementioning
confidence: 99%
“…The few available studies reporting on neuropsychiatric outcomes after GPi DBS have showed some improvement in mood and no major change in anxiety in primary dystonia [13][14][15][16]18,28,29 and more variable outcomes in secondary dystonia. 17,30,31 These reports have been limited by the small sample size, the relatively short follow-up (#36 months), and the lack of use of psychiatric interviews to assess patients.…”
Section: Classification Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…In most patients, DBS alleviates parkinsonian motor signs, shortens 'off' periods, and reduces druginduced dyskinesias, dystonia, and motor fluctuations (Rodriguez-Oroz et al, 2004;Anderson et al, 2005;Weaver et al, 2005;Portman et al, 2006;Bronstein et al, 2011). In general, both GPi-and STN-DBS are more effective than medical management alone to alleviate motor deficits in patients with advanced PD (Just and Ostergaard, 2002;Martinez-Martin et al, 2002;Troster et al, 2003;Lezcano et al, 2004;Diamond and Jankovic, 2005;Erola et al, 2005;Halbig et al, 2005;Lyons and Pahwa, 2005;Deuschl et al, 2006;Rodrigues et al, 2007a, b;Montel and Bungener, 2009;Weaver et al, 2009b;Zahodne et al, 2009). In contrast to patients with GPi-DBS, those with STN-DBS are often able to substantially reduce the medication doses (Breit et al, 2004; …”
Section: Current Surgical Targetsmentioning
confidence: 99%